Comparative genomics of the niche-specific plant pathogen Streptomyces ipomoeae reveal novel genome content and organization - Soares, Natasha R.; Huguet-Tapia, José C.; Guan, Dongli; Clark, Christopher A.; Yang, Kuei-Ting; Kluchka, Olivia R.; Thombal, Raju S.; Kartika, Rendy; Badger, Jonathan H.; Pettis, Gregg S. (Applied and environmental microbiology, 2023)
The sweet potato soil rot pathogen Streptomyces ipomoeae differs in disease pathology, host range, and virulence factor production from Streptomyces species that cause scab diseases on potato and other plant hosts. Nevertheless, previous phylogenomic analysis suggested S. ipomoeae and the oldest scab species, Streptomyces scabiei , are derived from a common ancestor. While genomes of scab pathogens have been described in some detail, similar knowledge of S. ipomoeae has been lacking. Here, we performed comparative genomic analyses involving both virulent and avirulent strains of S. ipomoeae, along with other plant-pathogenic and saprophytic Streptomyces spp. The txt gene cluster for the phytotoxin thaxtomin C was found in all virulent strains of S. ipomoeae , but, contrary to scab species, the thaxtomin locus does not appear to reside within a genomic island and has diverged from its scab pathogen counterparts. Increased TTA rare codon usage appears to be a hallmark of S. ipomoeae , and in particular, for its txt locus. The txtR activator gene, which we show here is essential for pathogenicity, appears to be subject to exceptional bldA translational control. Ortholog group searches identified genes found only in virulent S. ipomoeae strains in our analysis, and genome mining revealed secondary metabolite gene clusters of S. ipomoeae , which are not shared with scab species. Overall, we have identified novel aspects of genome organization and gene content consistent with niche development by S. ipomoeae , and the results here will facilitate the elucidation of the mechanisms governing its virulence and ecology. While most plant-pathogenic Streptomyces species cause scab disease on a variety of plant hosts, Streptomyces ipomoeae is the sole causative agent of soil rot disease of sweet potato and closely related plant species. Here, genome sequencing of virulent and avirulent S. ipomoeae strains coupled with comparative genomic analyses has identified genome content and organization features unique to this streptomycete plant pathogen. The results here will enable future research into the mechanisms used by S. ipomoeae to cause disease and to persist in its niche environment.